Muscle Imbalances: Testing and Training Functional Eccentric Hamstring Strength in Athletic Populations - Stastny, Petr; Lehnert, Michal; Tufano, James J (Journal of visualized experiments, 2018)
Many hamstring injuries that occur during physical activity occur while the muscles are lengthening, during eccentric hamstring muscle actions. Opposite of these eccentric hamstring actions are concentric quadriceps actions, where the larger and likely stronger quadriceps straighten the knee. Therefore, to stabilize the lower limbs during movement, the hamstrings must eccentrically combat against the strong knee-straightening torque of the quadriceps. As such, eccentric hamstring strength expressed relative to concentric quadricep strength is commonly referred to as the "functional ratio" as most movements in sports require simultaneous concentric knee extension and eccentric knee flexion. To increase the strength, resiliency, and functional performance of the hamstrings, it is necessary to test and train the hamstrings at different eccentric speeds. The main purpose of this work is to provide instructions for measuring and interpreting eccentric hamstring strength. Techniques for measuring the functional ratio using isokinetic dynamometry are provided and sample data will be compared. Additionally, we briefly describe how to address hamstring strength deficiencies or unilateral strength differences using exercises that specifically focus on increasing eccentric hamstring strength.
Keywords: Exercise Therapy; Humans; sporty; Quadriceps Muscle; Resistance Training; čtyřhlavý sval stehenní; odporový trénink; Adult; Muscle, Skeletal; mužské pohlaví; Sports; kosterní svaly; terapie cvičením; Male; dospělí; lidé